Early Childhood Education Services in Manzini Region in Eswatini: Equality and Accessibility - Bhebhe, Sithulisiwe; Vilakati, Ntokozo (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2021)
Every child is entitled to access quality early childhood education. Education services are meant to develop all individuals’ cognitive capacities, though this may vary with individuals given their variable genetic make-up. Early childhood education is one way in which children are developed for the future. This study sought to establish the accessibility and equality in the provision of early childhood education services to children in the Kingdom of Eswatini, Manzini region. Open-ended interviews were the instruments used for data collection. Thematic analysis was the data analysis method used in this study. The study found that in the Kingdom of Eswatini in Manzini region, not all children of early childhood going age go to school due to limited finances, poverty, and sicknesses. The study concluded that there is no equality in the provision of early childhood education, as privately-owned early childhood development centers were meant for the few who could afford, as most parents could not afford the fees. The study also found that some parents were not aware of the value of early childhood education. The study recommends that the Ministry of Education formulates a policy that will compel all children to attend early childhood education to achieve their goal of providing equal and quality education to all children in the country. The government of the Kingdom of Eswatini should pronounce the value of early childhood education and start funding preschool education and also provide a documented national curriculum to ensure equality.